Peran parenting dalam pendidikan karakter dan masa depan anak - Najiburrohman, Nur Muhammad (Maliki Interdisciplinary Journal, 2025)
The purpose of this article is to provide an understanding that the role of parents in educating the character and morals of young children is key to future success. Character education has a significant impact on the child’s personality, equipping them with the readiness to face life’s challenges in the future. This article discusses various aspects of parenting, including parenting styles, effective communication, and the role of parents in providing emotional support to their children. In addition, this article also discusses the importance of active parental involvement in the child’s daily life, such as through shared activities, instilling positive values from an early age, and setting a good example through behavior. Consistent involvement helps children feel valued, noticed, and emotionally secure. This, in turn, strengthens the bond between parents and children and supports optimal social and emotional development. Furthermore, the article highlights the influence of the family environment on the development of a child’s moral values, as well as how open and empathetic communication can help children better understand and manage their emotions. Therefore, it is expected that parents will understand that their role is irreplaceable in shaping a generation with strong character, noble morals, and the readiness to contribute positively to society in the future.